Applying Kahoot to Improve the Senior High School Students’ Vocabulary Achievement - Mansur, Moh; Fadhilawati, Dian (Universitas Hamzanwadi, 2019)
This research was a classroom action research which intended to improve the senior high school students? vocabulary achievement by applying Kahoot as learning media in the teaching and learning process. The research was conducted to 40 students from grade X of Islamic Senior High School (Madrasah) in Kota Blitar. The procedure in this research followed some steps based on Kemmis and Taggart model namely; 1) Planning, 2) Acting, 3) Observing and 4) Reflecting. The data collection of this research were taken from tests and questionnaire. The research showed that the use of Kahoot as media in teaching and learning vocabulary particularly in ?introducing oneself? could improve the students' vocabulary achievement. The pre-test showed that the students' score was 59.23). That score was under the minimum criterion mastery set by the school (75.00). After 1st cycle, there was an improvement on the students' score became 71.23 but it was still under minimum criteria. Therefore, it needed the 2nd cycle in which the score improved into 84.58. The improvement on the students? achievement was supported by the students? positive attitude toward the use of Kahoot in teaching and learning.